INFLUENCE OF ASCORBIC ACID ON THE PRO- AND ANTIOXIDANT POTATO SYSTEM IN CONDITIONS OF SALT STRESS - Chebonenko , O.V.; Amirkulova , A.Zh.; Tursunova , A.K.; Sapko , O.A.; Abayldaev , A.O.; Utarbayeva , A.Sh. (Eurasian Journal of Applied Biotechnology, 2017)
Ascorbic acid (AC) is a low-molecular antioxidant that plays a key role in regulating the level of reactive oxygen species (ROS) and products of lipid peroxidation (LPO) in plant cells and also participates in some physiological processes in plants. Ascorbic acid functions to remove many free radicals and to minimize the damaging effects of oxidative stress. Plants resistant to drought and salinity are characterized by higher levels of ascorbic acid, which are actively involved in the regulation of ROS under stress. We investigated the effect of exogenous ascorbic acid at a concentration of 10 mM on the activity of key antioxidant enzymes (AOEs): superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), peroxidase (POD), and pro-oxidant levels (H2O2, LPO) in the potato varieties ‘Axor’ and ‘Orbit’under conditions of salt stress. There were no significant varietal differences in the levels of pro- and antioxidant responses to ascorbic acid treatment. It was shown that ascorbic acid in shoots induced generation of H2O2 and reduced the level of LPO two-fold under salt stress. Ascorbic acid differentially regulates the activities of enzymes under saline conditions. The greatest impact of ascorbic acid was observed on SOD and APX in shoots, with a two-fold increase in their activity. The activity of CAT and POD increased 1.5–2-foldunder the combined effects of ascorbic acid and salinity. Thus, ascorbic acid can regulate the level of response of the antioxidant system of potato plants to salinity. Antioxidant enzymes have an active role in neutralizing ROS and adapting plants to stressful conditions.